2009
DOI: 10.1002/iroh.200811141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light and Wind Speed on the Vertical Distribution of Microcystis aeruginosa Colonies of Different Sizes during a Summer Bloom

Abstract: Different dynamics, of the vertical distribution of Microcystis aeruginosa colonies of different sizes, were examined in a large shallow lake (Taihu Lake) during a summer bloom. During the observation the Microcystis colonies, larger than 120 μm, were mainly concentrated in the upper layer both under calm and windy conditions. Colonies from 36 μm to 120 μm showed a clear relationship to wind conditions whereas colonies less than 36 μm showed a nearly uniform vertical distribution at the different depths. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 28 publications
(23 reference statements)
4
66
0
1
Order By: Relevance
“…Water blooms can be effectively predicted in numerical models that simulate the occurrence and disappearance of water blooms. The cyclic appearance and disappearance of water blooms is mainly driven by the spatial aggregation and dispersion of Microcystis by wind waves (Wu and Kong, 2009;Zhu et al, 2014). Consequently, this process is assumed in numerical simulations of blooms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water blooms can be effectively predicted in numerical models that simulate the occurrence and disappearance of water blooms. The cyclic appearance and disappearance of water blooms is mainly driven by the spatial aggregation and dispersion of Microcystis by wind waves (Wu and Kong, 2009;Zhu et al, 2014). Consequently, this process is assumed in numerical simulations of blooms.…”
Section: Introductionmentioning
confidence: 99%
“…In a laboratory study, Nakamura et al (1993) found that the measured floating velocity of Microcystis is proportional to colony size. Wu and Kong (2009) investigated Microcystis blooms in Lake Taihu, a large freshwater lake in the Yangtze Delta of Jiangsu Province, China. They found that large Microcystis colonies (>120 µm) can overcome wind-wave disturbance and thus accumulate at the water surface, whereas small colonies (<36 µm) tend to mix with the turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, these colonies may coalesce into free-floating mats or "scums" on the surface of the lake with a bright blue or bluegreen appearance due to the presence of C-phycocyanin, their major light harvesting pigment ( Figure 1). Colony size affects cyanobacterial vertical movement, and aids in diffusion of nutrients and signaling molecules between cells [68,69]. Large colony size resists predation by zooplankton (unlike other non-colonial algae) and filter feeding organisms including Dreissenids (e.g.…”
Section: Characteristics Of Bloom Forming Cyanobacteriamentioning
confidence: 99%
“…Large colony formation plays an important role in the occurrence of Microcystis blooms (Yamamoto et al 2011) because large colonies have higher speeds of vertical migration than smaller ones (Nakamura et al 1993) and this leads to accumulation near the water surface, thereby forming blooms (Wu & Kong 2009). …”
Section: Introductionmentioning
confidence: 99%